Hamstring reinjuries occur at the same location and early after return to sport. A descriptive study of MRI-confirmed reinjuries - Wangensteen, A.; Tol, J. L.; Witvrouw, E.; Van Linschoten, R.; Almusa, E.; Hamilton, B.; Bahr, R. (The American Journal of Sports Medicine, 2016)
Background: Despite relatively high reinjury rates after acute hamstring injuries, there is a lack of detailed knowledge about where and when hamstring reinjuries occur, and studies including imaging-confirmed reinjuries are scarce. Purpose: To investigate the location, radiological severity, and timing of reinjuries on magnetic resonance imaging (MRI) compared with the index injury. Study Design: Case series; Level of evidence, 4. Methods: A MRI scan was obtained =5 days after an acute hamstring index injury in 180 athletes, and time to return to sport (RTS) was registered. Athletes with an MRI-confirmed reinjury in the same leg =365 days after RTS were included. Categorical grading and standardized MRI parameters of the index injury and reinjury were scored by a single radiologist (with excellent intraobserver reliability). To determine the location of the reinjury, axial and coronal views of the index injury and reinjury were directly compared on proton density-weighted fat-suppressed images. Results: In the 19 athletes included with reinjury, 79% of these reinjuries occurred in the same location within the muscle as the index injury. The median time to RTS after the index injury was 19 days (range, 5-37 days; interquartile range [IQR], 15 days). The median time between the index injury and reinjury was 60 days (range, 20-316 days; IQR, 131 days) and the median time between RTS after the index injury and the reinjury was 24 days (range, 4-311 days; IQR, 140 days). More than 50% of reinjuries occurred within 25 days (4 weeks) after RTS from the index injury and 50% occurred within 50 days after the index injury. All reinjuries with more severe radiological grading occurred in the same location as the index injury. Conclusion: The majority of the hamstring reinjuries occurred in the same location as the index injury, early after RTS and with a radiologically greater extent, suggesting incomplete biological and/or functional healing of the index injury. Specific exercise programs focusing on reinjury prevention initiated after RTS from the index injury are highly recommended.